2017
DOI: 10.1088/1361-6560/aa5e99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MLACF based calculated attenuation brain PET imaging for FDG patient studies

Abstract: Calculating attenuation correction for brain PET imaging rather than using CT presents opportunities for low radiation dose applications such as pediatric imaging and serial scans to monitor disease progression. Our goal is to evaluate the iterative time-of-flight based maximum-likelihood activity and attenuation correction factors estimation (MLACF) method for clinical FDG brain PET imaging. FDG PET/CT brain studies were performed in 57 patients using the Biograph mCT (Siemens) four-ring scanner. The time-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In addition, its correlation with the “criterion standard” was not very good ( R 2 = 0.54). In this study, although the SNAC increased the SUV mean of different brain regions to a various degree, it was significantly correlated with CTAC results ( r = 0.988), consistent with a recent research ( r = 0.98) by Bal et al, [ 25 ] suggesting that the SNAC method is significantly improved compared with the traditional CAC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, its correlation with the “criterion standard” was not very good ( R 2 = 0.54). In this study, although the SNAC increased the SUV mean of different brain regions to a various degree, it was significantly correlated with CTAC results ( r = 0.988), consistent with a recent research ( r = 0.98) by Bal et al, [ 25 ] suggesting that the SNAC method is significantly improved compared with the traditional CAC.…”
Section: Discussionsupporting
confidence: 92%
“…Because of the presence of relatively low-density ventricular system in the brain, and CAC does not consider the attenuation coefficient of the sinus cavity and sinus cavity differences in different patients, which will lead to metabolic differences between the peripheral brain and mesial brain regions. [ 4 , 25 ] Zaidi et al [ 5 ] found that the relative difference of CAC's mean regional cerebral glucose metabolism was <8%. It has been shown that ignoring sinus air-like attenuation coefficient values can result in an overestimation of the tracer uptake by up to 20% in adjacent brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that emission-based attenuation correction is an active field of research, where large clinical validation studies have begun to emerge. A scale-corrected MLACF has recently been shown to provide images that quantitatively and visually correspond to CTAC-reconstructed PET images in 57 patients [131]. Benoit MLAA method was compared with state-of-the-art MRAC and CTAC, producing errors within a few percent [45].…”
Section: Emission-based Attenuation Correction Approaches For Pet/mrmentioning
confidence: 99%
“…However, another study (24) found that in a collection of 18 F-FDG brain scans, activity in the reconstructed activity images was more biased with the jointreconstruction method than with an atlas-based correction of attenuation. Finally, there was a study (25) in which the accuracy of another joint-reconstruction method-maximum-likelihood attenuation correction factors-was analyzed on a set of patient brain scans. The authors reported that the joint reconstruction was comparable to the gold standard once a plane-dependent scaling of the activity had been applied.…”
mentioning
confidence: 99%